Effect of statin use on the risk of medically attended acute respiratory illness among influenza vaccinated elderly. Issue 41 (1st October 2018) - Chiu, Hsien-Tsung; Shen, Li-Jiuan; Chen, Yee-Chun; Lin, Jung-Hsin; Wang, Chi-Chuan
Abstract: Objectives: The immunomodulatory effects of statins may reduce the immune response induced by influenza vaccines. However, evidence regarding the effect of statin use on the effectiveness of seasonal influenza vaccines against medically attended acute respiratory illness (MAARI) in the elderly remains scarce. Methods: We conducted a retrospective cohort study using data from Taiwan's National Health Insurance Research Database. Elderly adults aged ≧ 66 years who were vaccinated with seasonal influenza vaccines during the 2007–2008 to 2012–2013 influenza seasons were enrolled for this analysis. We compared the risk of MAARI between statin and non-statin users. Propensity score matching and conditional logistic regression models were used to analyze the data. Results: A total of 440, 180 elderly were included in this study. In general, the risk of MAARI was higher in statin users than non-statin users (odds ratio [OR]: 1.03, 95% confidence interval [CI]: 1.02–1.05). Statin exposure after vaccination was associated with a higher risk of MAARI (OR: 1.05, 95% CI: 1.02–1.07). Among different statin agents, simvastatin and lovastatin use was associated with a significant increase in the risk of MAARI (ORsimvastatin : 1.14, 95% CI: 1.10–1.18; ORlovastatin : 1.18, 95% CI: 1.12–1.25). Conclusions: Statin exposure, especially simvastatin and lovastatin, was associated with a higher risk of MAARI in the seasonal influenza vaccinated elderly. Future studies exploring the differences between individual statins and mechanisms of their immunomodulatory effects are necessary.